Incidence of Cochlear Nerve Deficiency in Unilateral Pediatric Auditory Neuropathy Spectrum Disorder - O'Rourke, Samuel P; Vos, Teresa G; Park, Lisa R; Culbertson, Shannon; Brown, Kevin D (Otolaryngology-head and neck surgery, 2025)
Determine the incidence of cochlear nerve deficiency in pediatric subjects with auditory neuropathy spectrum disorder in the setting of single-sided deafness. Retrospective chart review of pediatric subjects with single-sided deafness. Single tertiary care institution from January 2014 to October 2019. Subjects with unilateral severe-to-profound hearing loss were included if they had both magnetic resonance imaging and auditory brainstem response testing available. The incidence of auditory neuropathy spectrum disorder was assessed based on auditory brainstem response testing, and the incidence of cochlear nerve deficiency was determined from imaging review by a neurotologist. Mean pure tone audiometry at 500, 1000, and 2000 Hz of subjects within the auditory neuropathy spectrum disorder population was calculated. In total, 103 pediatric subjects were included. The incidence of auditory neuropathy spectrum disorder in this population was 30% (31 subjects). Within this group, 77.4% had cochlear nerve deficiency on imaging (24 subjects) and 22.6% (7 subjects) had normal cochlear nerves. Of the abnormal cochlear nerves, 18 nerves were aplastic and 6 hypoplastic. In subjects with auditory neuropathy spectrum disorder, there was no statistically significant difference in mean pure tone audiometry (P = .579) between ears with normal and deficient cochlear nerves. There is a high incidence of auditory neuropathy spectrum disorder in pediatric subjects with single-sided deafness, and the majority of ears with auditory neuropathy spectrum disorder also demonstrated cochlear nerve deficiency on imaging. It is imperative to pursue a thorough audiologic and radiographic work-up in this population to fully assess nerve status.